Broad Spectrum Antimicrobial Activity of Extracts of Jatropha curcas - Egharevba Henry Omoregie and Kunle Oluyemisi Folashade (Journal of Applied Pharmaceutical Science, 2013)
Jatropha curcas L. leaf and stem were extracted successively with hexane, ethylacetate, methanol and aqueous methanol. The extracts were tested in vitro for activity against standard strains microorganisms and clinical isolates. The zones of inhibition, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were determined. The organisms exhibited different degree of susceptibility to the inhibitory activity of the crude extracts. The zones of inhibition, MIC and MBC/MFC ranged from 14-37 mm, 1.25-10 mg/ml and 2.5-20 mg/ml for the susceptible organisms, respectively. The methanol extract was the most active and exhibited good activity against most food pathogens like Escherichia coli, Staphylococcus aureus, Salmonella typhimurium, Shigella dysenteriae, Psuedomonas aerugunosa, P. flourescenses, Klebsiella pneumonia and K. ozaenae. The highest activity was an MIC of 1.25 mg/ml and MBC of 2.5mg/ml. The activities observed could be due to the presence of some of the secondary metabolites like tannins, alkaloids, sterols, glycosides, saponins, terpenes and flavonoids which have been reported from the plant by other workers.
Keywords: Jatropha curcas, antimicrobial, v